Improvements on performance of bio-asphalt modified by castor oil-based polyurethane: An efficient approach for bio-oil utilization. (25th October 2021) - Liu, Jing; Lv, Songtao; Peng, Xinghai; Yang, Shuo
Highlights: Two kinds of bio-oils are used together in pavement materials to improve the utility. The response surface method is used to determine the optimal dosage of modifiers. The properties of bio-asphalt are evaluated from the macroscopic and microscopic perspectives. Abstract: Bio-asphalt is a potential pave material in road engineering. In order to realize comprehensive utilization of a variety of bio-oils and improve the road performance of bio-asphalt, this study chose two different sources of bio-oil for effective utilization. First, vegetable oil was used to prepare mixed bio-asphalt through high-speed shearing. Polyurethane and castor oil were added to the bio-asphalt for modification to obtain castor oil-based polyurethane-modified bio-asphalt (CPBA). Based on the Box-Behnken Design, the penetration test and softening point test of the CPBA were carried out to evaluate its conventional performance. Temperature sweep, multiple stress creep recovery test, and bending beam rheometer test was conducted to evaluate its macroscopic rheological properties. Fourier transform infrared reflection (FTIR) was shown to reveal its modification mechanism. Scanning electron microscopy (SEM) was performed to observe its microscopic morphology and verify the effect of polyurethane modification. The results manifest that castor oil-based polyurethane can increase the high-temperature properties of bio-asphalt. However, when the amount of castor oil is too high, it will also weaken the high-temperature properties of CPBA. The high-temperature properties of CPBA depend on castor oil content, polyurethane content, and stress level. Vegetable oil and castor oil can improve the low-temperature properties of asphalt. Instead, the chemical reaction production of polyurethane or polyurethane and castor oil with asphalt negatively influences the low-temperature properties of asphalt. The optimal polyurethane content, castor oil content, and vegetable oil content determined using the response surface method were equal to 20.00%, 33.61%, 8.38%. FTIR results manifest that polyurethane can chemically react with castor oil but not with vegetable oil. Vegetable oil mainly plays a role in improving the compatibility of CPBA. SEM results also show that under the action of vegetable oil, the appearance and structure of the reaction products of polyurethane and castor oil have been greatly improved. The polyurethane application in bio-asphalt makes a variety of bio-oil used, improving bio-asphalt performance and availability.